Carbodiimide inactivation of matrix metalloproteinases in radicular dentine. (March 2019) - Comba, Allegra; Scotti, Nicola; Mazzoni, Annalisa; Maravic, Tatjana; Ribeiro Cunha, Sandra; Michelotto Tempesta, Riccardo; Carossa, Massimo; Pashley, David H.; Tay, Franklin R.; Breschi, Lorenzo
Abstract: Objectives: The present in vitro study evaluated the effect of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC), a cross-linking agent used as an additional therapeutic primer for luting fiber posts to radicular dentine to prevent hybrid layer degradation. Methods: Root canal treatment was performed on 80 extracted single-rooted human teeth. A 10-mm post space was prepared and pecimens were randomly assigned to four groups (n=20) according to the bonding system: 1) All Bond 3 (Bisco); 2) All Bond 3 + 0.3M EDC; 3) Prime&Bond XP (Dentsply Sirona); 4) Prime&Bond XP + 0.3M EDC. In groups 2 and 4, EDC was applied on phosphoric acid-etched dentine for 1 min. Fiber posts (RelyX Fiber Post, 3M ESPE) were luted with a dual-cured resin cement (Core-X flow, Dentsply Sirona). Slices were prepared for micro push-out test and interfacial nanoleakage evaluation of the coronal and apical region of the canal space after 24 h and 1 year storage in artificial saliva. In-situ zymography was performed to investigate endogenous matrix metalloproteinase activities within the hybrid layer. Results were statistically analysed with three-way ANOVA test or Chi Square test. Statistical significance was set at α=0.05. Results: No significant influence was identified between the two adhesives. The use of EDC significantly improved fiber post bond strength at 1 year but not at 24 h. Application of 0.3 M EDC prior to bonding significantly reduced gelatinolytic activities within the radicular hybrid layers. Conclusions: Carbodiimide was effective in preserving fibre post bond strength over time, through reducing the activities of intra-radicular endogenous proteases. Clinical Significance: Inhibition of matrix metalloproteinases using EDC over radicular dentin could play an important role in bond strength preservation. However, the clinical relevance of these findings needs to be proven.